PERPETUAL FLOWERING2 coordinates the vernalization response and perennial flowering in Arabis alpina. (27th November 2018) - Lazaro, Ana; Zhou, Yanhao; Giesguth, Miriam; Nawaz, Kashif; Bergonzi, Sara; Pecinka, Ales; Coupland, George; Albani, Maria C
Abstract : The Arabis alpina APETALA2 ortholog, PERPETUAL FLOWERING2, coordinates the age-dependent response to vernalization and it is required to facilitate the activation of A. alpina FLOWERING LOCUS C after vernalization. Abstract: The floral repressor APETALA2 (AP2) in Arabidopsis regulates flowering through the age pathway. The AP2 ortholog in the alpine perennial Arabis alpina, PERPETUAL FLOWERING 2 ( PEP2 ), was previously reported to control flowering through the vernalization pathway via enhancing the expression of another floral repressor PERPETUAL FLOWERING 1 ( PEP1 ), the ortholog of Arabidopsis FLOWERING LOCUS C ( FLC ). However, PEP2 also regulates flowering independently of PEP1. To characterize the function of PEP2, we analyzed the transcriptomes of pep2 and pep1 mutants. The majority of differentially expressed genes were detected between pep2 and the wild type or between pep2 and pep1, highlighting the importance of the PEP2 role that is independent of PEP1 . Here, we demonstrate that PEP2 activity prevents the up-regulation of the A. alpina floral meristem identity genes FRUITFUL ( AaFUL ), LEAFY ( AaLFY ), and APETALA1 ( AaAP1 ), ensuring floral commitment during vernalization. Young pep2 seedlings respond to vernalization, suggesting that PEP2 regulates the age-dependent response to vernalization independently of PEP1. The major role of PEP2 through the PEP1 -dependent pathway takes place after vernalization, when it facilitates PEP1 activation both in the main shoot apex and in axillary branches. These multiple roles of PEP2 in the vernalization response contribute to the A. alpina life cycle.